2014
DOI: 10.5958/0976-5506.2014.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Education on Adoption of Immunization Services-A Case Control Study in Bhubaneswar, Odisha

Abstract: Back ground: Immunization is the most powerful and cost-effective weapon for the prevention and control and even eradication of a disease. So awareness about immunization among the parents is essential to immunize their children.Objective: The present study was done to assess the effect of maternal education on adoption of immunization practices. Materials and Method:Data was collected in the immunization clinic of Hi-Tech medical college and hospital from the mothers of children coming for immunization. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies have shown that awareness among mothers regarding optional vaccines is around 66 percent. (Patnaik, Mishra, and Choudhury 2014). Thus optional vaccines, since not available free of cost, have the potential to show gender disparity, if present, in case of vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that awareness among mothers regarding optional vaccines is around 66 percent. (Patnaik, Mishra, and Choudhury 2014). Thus optional vaccines, since not available free of cost, have the potential to show gender disparity, if present, in case of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Further qualitative research might be needed to find out the reasons behind this disparity that are amenable to corrections. By doing qualitative research probably we will get to know many themes (Angelillo et al 1999;Patnaik, Mishra, and Choudhury 2014) like lack of knowledge of parents about the importance of vaccination for female children; importance of various socio-demographic factors leading to gender disparity; education of the decision maker in the family for financial aspects (usually father); target for health education (father/ mother/ both); or approaches in communication for health education.…”
Section: Group Of Experts On Immunization 2014)mentioning
confidence: 99%
See 1 more Smart Citation